Respuestas
Respuesta dada por:
64
Respuesta dada por:
37
Factorizar.
Caso.
Factor comun por agrupación de terminos.
3x³ - 9ax² - x + 3a = Agripas.
(3x³ - 9ax²) - (x - 3a) = Sacas factor comun 3x²
3x²(x - 3a) - (x - 3a) = Sacas factor comun (x - 3a)
(x - 3a)(3x² - 1)
Respuesta.
(x - 3a)(3x² - 1)
Caso.
Factor comun por agrupación de terminos.
3x³ - 9ax² - x + 3a = Agripas.
(3x³ - 9ax²) - (x - 3a) = Sacas factor comun 3x²
3x²(x - 3a) - (x - 3a) = Sacas factor comun (x - 3a)
(x - 3a)(3x² - 1)
Respuesta.
(x - 3a)(3x² - 1)
Preguntas similares
hace 7 años
hace 7 años
hace 9 años
hace 9 años
hace 9 años